Суспільно-політичні публікації на сторінках чернівецької «Самостійної Думки» (1931-1937) як джерело соборницьких ідей - Попович, Юлія Олександрівна (Сумський державний університет, 2017)
The article gives the analysis of the publications on socio-political issues that played a significant role in the formation of national consciousness of Bukovinian Ukrainians towards an independent and united Ukraine. The main focus is on the content of the article, including state ideas and genre specifity of more than two dozen published materials, the authors of which were mainly Ukrainian leaders of nationalistic movement – D. Andriyevskyy, S. Lakusta, V. Lypynskyy, Yevhen Onatsky, M. Rayhorodskyy, M .Stsiborskyy and others. Due to elaborated analysis we may conclude that the ideas expressed by authors mentioned above is a certain contribution to the development of the theory of state and development of the Ukrainian nationalistic movement, including Bukovina as well.
Socio-political articles on the pages of Chernivtsi magazine «Samostiyna dumka» (1931–1937) as the source of ideas of unity
Keywords: часопис, соборність, самостійність, державотворення, націоналізм; magazine, unity, independence, state, nationalism